TEXTBOOKS AND TEMPLATES IN BYZANTINE STUDIES - Matthew Gray Marsh (Journal of Ancient History and Archaeology)
Though the modern study of Byzantine civilisation and history dates back to the late 19th century, the establishment of a definitive introductory textbook in the English language would be a slow process that would not culminate until the 1950’s. Due in part to the enormous chronological termini of Byzantine History, and major primary sources in at least five different languages, the number of introductory works is much smaller than in other historical disciplines. As a result, Byzantine history textbooks are still very closely welded to two initial templates established in 1892 and 1925. This article will briefly examine the initial templates laid down by the early authors of Byzantine textbooks.  Following the examination of these templates, we will move chronologically through some of the main publications of the long 20th century, concluding in the present day, gauging the impact of these works through scholarly reaction and publication information.